Single- A nd multicomponent fixed bed adsorption of CO2, CH4, and N2in binder-free beads of 4A zeolite - Zafanelli, Lucas F.A.S. (2018)
Single- A nd multicomponent adsorption fixed bed breakthrough experiments of carbon dioxide (CO2), methane (CH4), and nitrogen (N2) on commercial binder-free beads of 4A zeolite have been studied at 313, 373, and 423 K and a total pressure of up to 5 bar. The ternary experiments (CO2/CH4/N2) show a practically complete separation of CO2 from CH4/N2 at all the temperatures studied, with selectivity at 313 K of CO2 around 24 over CH4 and 50 over N2. The adsorption equilibrium data measured from the breakthrough experiments were modeled by the dual-site Langmuir isotherm, and the breakthrough results were simulated with a fixed bed adsorption model taking into account axial dispersion, mass-transfer resistances, and heat effects. The mathematical model predicts with a good accuracy the systematic behavior of the single- A nd multicomponent breakthrough results based on the independent parameters calculated from well-established correlations and intracrystalline diffusivities for zeolite 4A available in the literature. The results showed in the present work evidence that the binder-free beads of zeolite 4A can be employed to efficiently separate CO2 from CO2/CH4/N2 mixtures by fixed bed adsorption.